2021
DOI: 10.1177/1078155220987291
|View full text |Cite
|
Sign up to set email alerts
|

Does nutritional status affect treatment tolerability, chemotherapy response and survival in metastatic gastric cancer patients? Results of a prospective multicenter study in Turkey

Abstract: Background The possible impact of malnutrition on the efficacy and tolerability of modern chemotherapy for metastatic gastic adenocarcinoma (mGC) patients is unclear. With this study, we aimed to represent the possible impact of malnutrition on the efficacy and tolerability of chemotherapy, and also on the overall survival of mGC patients. Methods In this prospective multicenter study, we collected demographic, oncological and nutritional data of our mGC patients. The nutritional status of patients were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Their results indicated that the NRI was related to a shorter survival time. Other studies on gastric cancer had also reached similar conclusions (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 62%
“…Their results indicated that the NRI was related to a shorter survival time. Other studies on gastric cancer had also reached similar conclusions (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 62%
“…The study characteristics reveal that among the 30 studies examined (Table 1AB), the majority of studies had observational cohort study designs (n = 24 for prospective study design [7,[31][32][33][34][36][37][38][39][40][41][42][44][45][46][47][48][51][52][53][54][57][58][59], n = 5 for retrospective study design [35,43,49,55,56], while one study used a randomized control trial (RCT) [50].) Among 24 prospective studies, six studies [31,42,47,51,54,57] used longitudinal follow-up assessing chemotoxicity from baseline to after chemotherapy with multiple time points (at every cycle over 8 cycles [47,54]; at every 3 months over one year [51]; at every cycle over 12 cycles [31]; at weekly over a month [42]; at monthly over 3 months [57]) over the course of chemotherapy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample sizes ranged from 2,691 [40] to 52 [33], and the sample sizes were between > 100 and < 500 in the majority of studies (n = 16). Among 30 studies, 24 studies [7,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]53,55,57] identified significant risk factors of chemotoxicity; 10 studies [31,33,37,39,40,43,46,[48][49][50] examined the differences of chemotoxicity by categorical groups (i.e., high, versus low values) of risk factors; 11 studies reported odds ratios [ORs] [34][35][36]38,41,44,45,47,51,53,55,57]; and 2 st...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with digestive cancer, several studies show that moderate-to-severe malnutrition increases the toxicity of chemotherapy as well as decreased overall survival [123][124][125][126].…”
Section: Response To Treatment and Mortalitymentioning
confidence: 99%